Analysis Of Potential And Development Purwabakti Tourism Village, Bogor District - Salmah; Yudha, Aditya Prima; Andria, Fredi; Salsabila, Amalia Salwa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Purwabakti Tourism Village has great tourism potential, but the number of tourist visits is still low. In 2023, the village only received an average of 50 tourists per month, or around 0.19% of the total domestic tourists in Pamijahan Sub-district. Some of the factors that cause the low number of visits are not optimal tourism management, lack of supporting facilities, limited accessibility, and lack of promotion. This study aims to analyze the internal and external factors that influence the development of Purwabakti Tourism Village using SWOT analysis and formulate the right strategy to increase the village's tourism attractiveness. This research uses a descriptive qualitative method with data collection through interviews with the Tourism Awareness Group (Pokdarwis), tourism managers, and representatives of the Bogor Regency Culture and Tourism Office. Field observations were also conducted to assess the condition of village tourism. Data were analyzed using SWOT analysis, then strategies were developed through TOWS Matrix In addition, strategy evaluation was conducted using the IFE (Internal Factor Evaluation) Matrix and the EFE (External Factor Evaluation) Matrix to determine the village's strategic position. The results showed that Purwabakti Tourism Village is in cell 6 in the IE Matrix, so the recommended strategy is the harvest strategy. This strategy focuses on optimizing existing resources to increase revenue without large investments. The main recommendations include improving tourism infrastructure, increasing promotion, and maintaining tourism sustainability. Through the implementation of this strategy, it is expected that the number of tourist visits will increase and the village can contribute more to the local economy.